Boosting productivity in the United Kingdom's service sectors - Mourougane, Annabelle (OECD Economics Department Working Papers, 2020)
The United Kingdom has been among the most affected OECD economies by the COVID-19 crisis, reflecting the high share of services in output and its integration in the world economy. Productivity growth in the United Kingdom has consistently underperformed relative to expectations and was more disappointing than in most other OECD economies since at least the global financial crisis. Sluggish productivity growth in the service sectors was the main factor behind this weak performance. Raising productivity will help to sustain employment and wages but will require a broad range of policies. Keeping low barriers to trade and competition in the UK service sectors will create a supportive environment for strong productivity performance. Prioritising digital infrastructure in the allocation of the planned increase in public investment is expected to bring large productivity dividends. Reviewing the system of support to small firms in the light of the COVID-19 crisis will help to re-prioritise resources towards young innovative firms. Further increasing public spending on training to develop the digital skills of low-qualified workers, which have been particularly affected by the COVID-19 crisis, will be a double-dividend policy, boosting productivity and lowering inequality